Effect of service quality on inpatient satisfaction at Cibinong Regional General Hospital - Ichsan Trisutrisno (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Patient satisfaction is a key indicator in evaluating the quality of healthcare services. Understanding the influence of service quality dimensions helps hospitals improve patient experience and service performance. Methods: This descriptive-analytic study employed a cross-sectional design and included 60 inpatients selected by simple random sampling. Data were collected using a SERVQUAL-based questionnaire assessing five dimensions: reliability, tangibles, assurance, responsiveness, and empathy. Statistical analysis was performed using the Chi-Square test with α = 0.05. Result: Most respondents (65%) reported being satisfied. All dimensions of service quality showed significant relationships with patient satisfaction: reliability (p = 0.001), tangible (p = 0.001), assurance (p = 0.023), responsiveness (p = 0.003), and empathy (p = 0.002). These findings indicate that inpatient satisfaction is influenced by consistent service performance, physical facility conditions, professional competence, responsiveness, and empathetic attitudes. Conclusion: Service quality dimensions significantly affect inpatient satisfaction. Strengthening all five SERVQUAL dimensions is essential for enhancing service quality and improving overall patient experience at RSUD Cibinong.